1995
DOI: 10.1177/1045389x9500600117
|View full text |Cite
|
Sign up to set email alerts
|

Truss Structure Integrity Identification Using PZT Sensor-Actuator

Abstract: This paper presents a frequency domain impedance-signature-based technique for health monitoring of an assembled truss structure. Unlike conventional modal analysis approaches, the technique uses piezoceramic (PZT) elements as integrated sensor-actuators for acquisition of signature pattern of the truss. The concept of the localization of sensing/actuation area for damage detection of an assembled structure is presented for the first time. Through a PZT patch bonded to a truss node and the measurement of its e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
296
0
21

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 367 publications
(318 citation statements)
references
References 2 publications
1
296
0
21
Order By: Relevance
“…These early works demonstrated that a permanently attached PWAS can be used as a structural-identification sensor since the PWAS terminals reflect the coupled-system dynamics. The E/M impedance method was first used for SHM to detect damage in a truss structure by Sun, et al [47]. It was first shown to have extreme sensitivity to local damage and insensitivity to far-field damage in the tail section of a Piper Model 601P airplane [48].…”
Section: Electro-mechanical Impedance Methodsmentioning
confidence: 99%
“…These early works demonstrated that a permanently attached PWAS can be used as a structural-identification sensor since the PWAS terminals reflect the coupled-system dynamics. The E/M impedance method was first used for SHM to detect damage in a truss structure by Sun, et al [47]. It was first shown to have extreme sensitivity to local damage and insensitivity to far-field damage in the tail section of a Piper Model 601P airplane [48].…”
Section: Electro-mechanical Impedance Methodsmentioning
confidence: 99%
“…Therefore, the real part of the electrical impedance is commonly used for SHM applications. (Sun, et al 1995) For SHM applications, impedance methods are similar to traditional vibrations techniques in that both methods aim to monitor the structural integrity of a structure by observing changes in its characteristic vibrations over time. An extensive review of SHM techniques based upon traditional vibrations is given in Doebling, et al (1998).…”
Section: Testing Parameters Involved With Impedance Methodsmentioning
confidence: 99%
“…For this reason, a few frequency ranges are normally chosen, and ideally each frequency range contains 20 to 30 peaks. (Sun, et al 1995) Because of the relatively high frequencies involved, impedance methods are generally more sensitive to local changes in a structure, and traditional vibrations techniques are generally more sensitive to global changes in the structure. With impedance measurements, "a frequency range higher than 200-kHz is found to be favorable in localizing the sensing, while a frequency range lower than 70-khz covers a larger sensing area."…”
Section: Testing Parameters Involved With Impedance Methodsmentioning
confidence: 99%
See 2 more Smart Citations